(untitled) (Journal of Enam Medical College, 2013)
Background: Over half-a-million women die each year from pregnancy-related causes, and 99 percent of these occur in developing countries. In Bangladesh though maternal mortality rate (MMR) declined significantly around 40% in the past decade, still eclampsia accounts for 20% of maternal deaths. Eclampsia is uniquely a disease of pregnancy, and the only cure is delivery regardless of gestational age. A rational therapy for general management of hypertension and convulsion has been established in Bangladesh by the Eclampsia Working Group. But controversy still exists regarding obstetric management. Objective: To evaluate the feto-maternal outcome in cesarean section compared to vaginal delivery in eclamptic patients. Materials and Methods: This prospective cohort study was conducted in the department of Obstretics & Gynecology, Dhaka Medical College & Hospital (DMCH), from January to December 2011. A total 100 eclamptic women with term pregnancy and live foetus were purposively included in the study (Group I, 50 patients with vaginal delivery and Group II, 50 with cesarean section). Results: Out of these 100 patients 56% were aged <20 years, 71% were primigravida and 77% were from low socioeconomic status. Sixteen percent patients from vaginal delivery group and 18% from cesarean section group had no antenatal care. The mean gestational age was about 38 weeks in two groups. No significant difference was found between the two groups regarding blood pressure, proteinuria, consciousness level and convulsion. Recurrence of convulsion occurred in 30% patients of vaginal delivery group compared to 6% in cesarean section group. Maternal complications such as postpartum hemorrhage, cerebrovascular accident, renal failure, obstetric shock and abruptio placenta were higher among vaginal delivery group patients (46%) than cesarean section patients (16%). Maternal mortality was 6% in the vaginal delivery group and none in the cesarean section group. Regarding fetal outcome, stillbirth was 20% after vaginal delivery and 6% after cesarean section, the result was statistically significant. Birth asphyxia was less in the cesarean section group (23.4%) than in vaginal delivery group (60%) and this was statistically significant. Conclusions: The result of the present study shows a better feto- maternal outcome in the cesarean section group than in the vaginal delivery group. Journal of Enam Medical College; Vol 3 No 2 July 2013; Page 77-83 DOI: http://dx.doi.org/10.3329/jemc.v3i2.16128